Neurological autoimmune diseases following vaccinations against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2): A follow‐up study. (2nd November 2022) - Doubrovinskaia, Sofia; Mooshage, Christoph M.; Seliger, Corinna; Lorenz, Hanns‐Martin; Nagel, Simon; Lehnert, Pascal; Purrucker, Jan; Wildemann, Brigitte; Bendszus, Martin; Wick, Wolfgang; Schönenberger, Silvia; Kaulen, Leon D.
Abstract: Background and purpose: Population‐based studies suggest severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccines may trigger neurological autoimmunity including immune‐mediated thrombotic thrombocytopenia. Long‐term characterization of cases is warranted to facilitate patient care and inform vaccine‐hesitant individuals. Methods: In this single‐center prospective case study with a median follow‐up of 387 days long‐term clinical, laboratory and imaging characteristics of patients with neurological autoimmunity diagnosed in temporal association (≤6 weeks) with SARS‐CoV‐2 vaccinations are reported. Results: Follow‐up data were available for 20 cases (central nervous system demyelinating diseases n = 8, inflammatory peripheral neuropathies n = 4, vaccine‐induced immune thrombotic thrombocytopenia n = 3, myositis n = 2, myasthenia n = 1, limbic encephalitis n = 1, giant cell arteritis n = 1). Following therapy, the overall disability level improved (median modified Rankin Scale at diagnosis 3 vs. 1 at follow‐up). The condition of two patients worsened despite immunosuppressants possibly related to their autoimmune diagnoses (limbic encephalitis n = 1, giant cell arteritis n = 1). At 12 months' follow‐up, 12 patients achieved complete clinical remissions with partial responses in five and stable disease in one case. Correspondingly, autoimmune antibodies were non‐detectable or titers had significantly lowered in all, and repeat imaging revealed radiological responses in most cases. Under vigilant monitoring 15 patients from our cohort underwent additional SARS‐CoV‐2 vaccinations (BNT162b2 n = 12, mRNA‐1273 n = 3). Most patients ( n = 11) received different vaccines than prior to diagnosis of neurological autoimmunity. Except for one short‐lasting relapse, which responded well to steroids, re‐vaccinations were well tolerated. Conclusions: In this study long‐term characteristics of neurological autoimmunity encountered after SARS‐CoV‐2 vaccinations are defined. Outcome was favorable in most cases. Re‐vaccinations were well tolerated and should be considered on an individual risk/benefit analysis. Abstract : In this study we define long‐term characteristics of various neurological autoimmune disorders encountered after SARS‐CoV‐2 vaccinations. Long‐term outcome was favorable in most cases. Re‐vaccinations were well‐tolerated and should be considered on an individual risk/benefit analysis.